Kepuasan Masyarakat Terhadap Pelayanan Jasa Pembayaran Pajak Kendaraan Bermotor (PKB) Roda Dua Di Samsat Kota Pontianak - Sinhan 01 (JURNAL MANAJEMEN MOTIVASI, 2014)
The purpose of this study was to determine the taxpayer's satisfaction with quality of services in the motor vehicle tax payments SAMSAT Pontianak. The analysis is the Cartesian diagram. The population in this study is the taxpayer motorcycle tax payment in Pontianak City SAMSAT with the sample of 100 respondents. Based on the survey results revealed that there is a difference between the value of the benefit and satisfaction of - 0.1 which means that the interests of the respondents is greater than the satisfaction of respondents. Tangible variables are in quadrant A (4:28: 4:45), which shows the factors or attributes that are considered to affect the satisfaction of taxpayers, including elements of the services that are considered very important, but SAMSAT Pontianak City has not done as you wish taxpayer so disappointing / not satisfied and necessary to the improvement of services. Variable reliability (4:31: 4:48), responsiveness (4:31: 4:43), and assurance (4:42: 4:46) are in quadrant B, which means that these variables are variables that directly influence customer satisfaction, and its implementation by SAMSAT Pontianak is considered a good and shall be maintained. Variable empathy (4.27: 4.30) are in quadrant C, which means that these variables are variables that are considered less important to the customer, but the implementation by the company is still not satisfactory.